2021
DOI: 10.3892/etm.2021.9781
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR‑1184 serves as a diagnostic biomarker in neonatal sepsis and regulates LPS‑induced inflammatory response by inhibiting IL‑16 in monocytes

Abstract: Neonatal sepsis (NS) remains a global problem. In the present study, abnormal expression of microRNA-1184 (miR-1184) was detected in neonates with NS and it was endeavored to investigate the diagnostic value of miR-1184, as well as its regulatory role in lipopolysaccharide (LPS)-induced inflammatory response in vitro. Furthermore, the correlation between interleukin-16 (IL-16) and miR-1184 was investigated to elucidate the pathological mechanisms of NS development. Reverse transcription-quantitative PCR was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“… 29 Although blood culture is the gold standard for sepsis, identification is complicated by high false-negative results. 6 The APACHE II score and SOFA score are widely used to assess sepsis risk and prognosis; however, multiple measurements are required due to their poor specificity. 30 Therefore, we analyzed the correlation between serum miR-486-5p and common diagnostic criteria PCT, CRP, APACHE II, and SOFA score by Spearman coefficient analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 Although blood culture is the gold standard for sepsis, identification is complicated by high false-negative results. 6 The APACHE II score and SOFA score are widely used to assess sepsis risk and prognosis; however, multiple measurements are required due to their poor specificity. 30 Therefore, we analyzed the correlation between serum miR-486-5p and common diagnostic criteria PCT, CRP, APACHE II, and SOFA score by Spearman coefficient analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of miRNAs is not only participated in the important biological functions of disease but also proposed as a diagnostic and predictive biomarker due to its conservation and stability. 5 As the abnormal miR-1184, 6 miR-22-3p, 7 and miR-452 8 have been proved to be potential biomarkers of sepsis. Among many miRNAs, miR-486-5p is located on human chromosome 8p11.21 and can be used as a potential biomarker for sarcopenia in the elderly, 9 endometrial cancer, 10 and chronic myelogenous leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggests that miRNAs play vital roles in immune regulation in autoimmune and infectious diseases [ 22 , 23 ]. Various biomarkers have been considered to aid the diagnosis and prognosis of sepsis, but with limitations in severe and early cases [ 2 , 3 ]. Recently, much attention has focused on utilizing serum miRNAs as biomarkers for the diagnosis and prognosis of sepsis that are released outside cells into serum and remain stable in circulation, given their ease of detection [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous biomarkers for the diagnosis and detection of sepsis at an early stage have been identified, such as C-reactive protein (CRP), procalcitonin (PCT), and interleukins (ILs), but they have poor specificity [ 2 ]. Blood culture is widely used in the diagnosis of sepsis, but the results of culture may be delayed and false negative results are often obtained [ 3 5 ]. Therefore, there is an urgent need to identify novel biomarkers for discriminating sepsis at an early stage in addition to the possibility of their use as therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, Wang et al have shown significant downregulation of miR-1184 in septic neonates and correlation with levels of serum pro-inflammatory cytokines Il-1β, IL-6, and TNF-α. Artificial overexpression of this miRNA improved inflammatory response in LPS-induced monocytes ( 75 ).…”
Section: Micrornas As Promising Biomarkers Of Neonatal Sepsismentioning
confidence: 99%